1993
DOI: 10.3382/ps.0721245
|View full text |Cite
|
Sign up to set email alerts
|

Liquid Methionine Hydroxy Analog (Free Acid) and DL-Methionine Attenuate Calcium-Induced Kidney Damage in Domestic Fowl

Abstract: To evaluate the possibility that kidney damage may be induced by the commercial practice of feeding high-Ca (HCa) prelayer rations, and to evaluate the protective efficacy of supplementing HCa diets with liquid methionine hydroxy analog free acid or DL-methionine, 12-wk-old female Single Comb White Leghorn pullets were fed one of the following corn-soybean meal-based diets until they reached 22 wk of age: normal-Ca (NC, 1% Ca); HCa (HC, 3.5% Ca); HCa supplemented with .34 or .68% liquid methionine hydroxy anal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0

Year Published

1994
1994
2019
2019

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 42 publications
1
5
0
Order By: Relevance
“…Urinary uric acid excretion in birds with severe kidney damage caused by the HC and HCHP diets was not significantly less than in the control, suggesting that increased plasma uric acid is not the result of decreased urinary uric acid excretion. Our results also supported a previous study showing that plasma uric acid concentrations are not directly related to calcium-induced kidney damage (Wideman et al, 1993). Other factors such as the higher protein ingested in HCHP may have increased plasma uric acid.…”
Section: Discussionsupporting
confidence: 93%
“…Urinary uric acid excretion in birds with severe kidney damage caused by the HC and HCHP diets was not significantly less than in the control, suggesting that increased plasma uric acid is not the result of decreased urinary uric acid excretion. Our results also supported a previous study showing that plasma uric acid concentrations are not directly related to calcium-induced kidney damage (Wideman et al, 1993). Other factors such as the higher protein ingested in HCHP may have increased plasma uric acid.…”
Section: Discussionsupporting
confidence: 93%
“…These "acidifiers" consistently function effectively in spite of the fact that urinary Ca apparently is a limiting constituent required for avian Ca-urate urolith formation, and urinary Ca excretion increases significantly (hypercalciuria) when plasma Ca concentrations are elevated in pullets fed urinary acidifiers (Oldroyd and Wideman, 1986;Glahn et al, 1988a;Wideman et al, 1989;Lent and Wideman, 1994). The latter observation raises the possibility that the hypercalciuria triggered by urinary acidification could interfere with Ca utilization, potentially affecting crucial variables such as bone mineralization, egg production, and eggshell quality (Mongin, 1968;Glahn et al, 1988b;Wideman et al, 1993).…”
Section: Introductionmentioning
confidence: 86%
“…Previous (Lent and Wideman, 1993;Wideman et al, 1989Wideman et al, , 1993; nor were SCWL hens in full production affected when their diets were supplemented with either 1% ammonium chloride or 1% DLM (Glahn et al, 1988b;Koelkebeck et al, 1991). However, the impact of very high (>1%) levels of DLM and HMB on SCWL hens previously had not been evaluated; therefore the present study was designed to evaluate the responses of laying hens to diets containing up to 2% DLM or equimolar (2.25%) HMB.…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…However, the beneficial effects of calcium can only be attained when the recommended doses are administered. Many metabolic problems, such as diuresis, urolithiasis, visceral gout, and poor pullet performance have been reported to be associated with excessive dietary calcium (Siller, 1981;Wideman and Cowen, 1987;Leeson and Summers, 1987;Wideman et al, 1993;Guo et al, 2005;Julian, 2005). Case histories of affected bird flocks often revealed that excessive calcium had been fed.…”
Section: Introductionmentioning
confidence: 97%